2017
DOI: 10.1049/el.2016.4539
|View full text |Cite
|
Sign up to set email alerts
|

3.125 Gbit/s CMOS transceiver for duobinary modulation over 50‐m SI‐POF channels

Abstract: This Letter presents a novel CMOS transceiver for short-reach multigigabit communication over step-index plastic optical fibre (SI-POF), a very interesting transmission medium for industrial and home-end applications due to its low cost, ease of handling and inherent immunity to electromagnetic interference. The transceiver uses amplitude duobinary modulation, which is added to continuous-time equalisation. For that purpose, a duobinary precoder and a duobinary decoder have been fabricated in a standard 0.18-µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Due to increasing numbers of emerging services, such as intelligent home systems, visible light communications, etc., in indoor networks, the increase of high-capacity demand shifts from long-haul systems to short-range communication links. Indeed, POFs are good candidates for short-range communications [13][14][15][16][17][18][19][20][21], with low weight and high transmission capacity. Accordingly, Professor Koike and his research group demonstrated data transmission over POF in 1995 [22], where they reported 2.5 Gb/s 100 m data transmission using GI POF at 650 nm wavelength; more recently, in 2016, they developed 120 Gb/s GI POF, as well as the ballpoint pen interconnection technology 2 of 18 for uncompressed 4K/8K video transmission [23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to increasing numbers of emerging services, such as intelligent home systems, visible light communications, etc., in indoor networks, the increase of high-capacity demand shifts from long-haul systems to short-range communication links. Indeed, POFs are good candidates for short-range communications [13][14][15][16][17][18][19][20][21], with low weight and high transmission capacity. Accordingly, Professor Koike and his research group demonstrated data transmission over POF in 1995 [22], where they reported 2.5 Gb/s 100 m data transmission using GI POF at 650 nm wavelength; more recently, in 2016, they developed 120 Gb/s GI POF, as well as the ballpoint pen interconnection technology 2 of 18 for uncompressed 4K/8K video transmission [23].…”
Section: Introductionmentioning
confidence: 99%
“…The use of techniques to enhance the bandwidth of the communication link, such as equalization or baseband modulation, is mandatory to exceed 1 Gbps in short-range communications. In this frame, duobinary baseband modulation is a very interesting option because it offers the best trade-off between the three most important features of a modulation scheme: data rate, signal to noise ratio (SNR) and power consumption [1]. Duobinary doubles the data rate with respect to standard NRZ modulation by simple and low-power circuitry, without suffering as much SNR penalty as other modulation formats, like 4-PAM.…”
Section: Introductionmentioning
confidence: 99%
“…Ωστόσο, δεν είχε βελτιστοποιηθεί το κομμάτι της εκπομπής όσον αφορά την επίδραση φαινομένων μη γραμμικότητας της πηγής. Λαμβάνοντας υπόψη τα ευνοϊκά χαρακτηριστικά του Duobinary σχήματος διαμόρφωσης, κατασκευάστηκε κατάλληλο κύκλωμα προ-κωδικοποίησης και αποκωδικοποίησης για την επεξεργασία σημάτων διαμορφωμένα κατά το συγκεκριμένο σχήμα διαμόρφωσης [79]. Σε φάση σχεδιασμού, εξετάστηκε η μετάδοση σήματος σε ρυθμό 3.125 Gbit/s (με BER = 10 -12 και ευαισθησία -15 dBm) κατά μήκος 50 μέτρων SI-POF, θεωρώντας εξίσωση καναλιού στο δέκτη αποδίδοντας εξισωμένη ζεύξη εύρους ζώνης 700 MHz [79].…”
Section: πλεονεκτήματα μειονεκτήματα και δυνατότητες αξιοποίησης των πλαστικών οπτικών ινώνunclassified